Calcium palmitate: A green corrosion inhibitor for steel in concrete environment - Quraishi M.A.; Kumar V.; Singh B.N.; Singh S.K. (My University, 2025)
In the present investigation the effect of calcium palmitate alone and in combination with calcium nitrite on corrosion of steel was investigated. The effect of inhibitor on consistency, soundness, setting times of cement, compressive strength cement and concrete was also studied .The results of the investigation demonstrated that calcium palmitate is an effective inhibitor. PN5 and PN6 showed 92 % and 91% IE respectively after 90 days of exposure in 3.5% NaCl solution without effecting the mechanical strength of cement and concrete Petrographic examination reveals that calcium palmitate blocs the pores and thereby reduces the corrosion rate of steel In photographic examination of steel inhibited steel is found to be more smooth as compared to blank.